Tumour biomarkers: association with heart failure outcomes. (5th May 2020) - Shi, C.; van der Wal, H. H.; Silljé, H. H. W.; Dokter, M. M.; van den Berg, F.; Huizinga, L.; Vriesema, M.; Post, J.; Anker, S. D.; Cleland, J. G.; Ng, L. L.; Samani, N. J.; et al.
Abstract: Background: There is increasing recognition that heart failure (HF) and cancer are conditions with a number of shared characteristics. Objectives: To explore the association between tumour biomarkers and HF outcomes. Methods: In 2, 079 patients of BIOSTAT‐CHF cohort, we measured six established tumour biomarkers: CA125, CA15‐3, CA19‐9, CEA, CYFRA 21‐1 and AFP. Results: During a median follow‐up of 21 months, 555 (27%) patients reached the primary end‐point of all‐cause mortality. CA125, CYFRA 21‐1, CEA and CA19‐9 levels were positively correlated with NT‐proBNP quartiles (all P < 0.001, P for trend < 0.001) and were, respectively, associated with a hazard ratio of 1.17 (95% CI 1.12–1.23; P < 0.0001), 1.45 (95% CI 1.30–1.61; P < 0.0001), 1.19 (95% CI 1.09–1.30; P = 0.006) and 1.10 (95% CI 1.05–1.16; P < 0.001) for all‐cause mortality after correction for BIOSTAT risk model (age, BUN, NT‐proBNP, haemoglobin and beta blocker). All tumour biomarkers (except AFP) had significant associations with secondary end‐points (composite of all‐cause mortality and HF hospitalization, HF hospitalization, cardiovascular (CV) mortality and non‐CV mortality). ROC curves showed the AUC of CYFRA 21‐1 (0.64) had a noninferior AUC compared with NT‐proBNP (0.68) for all‐cause mortality ( P = 0.08). A combination of CYFRA 21‐1 and NT‐proBNP (AUC = 0.71) improved the predictive value of the model for all‐cause mortality ( P = 0.0002 compared with NT‐proBNP). Conclusions: Several established tumour biomarkers showed independent associations with indices of severity of HF and independent prognostic value for HF outcomes. This demonstrates that pathophysiological pathways sensed by these tumour biomarkers are also dysregulated in HF. Abstract :